DIGITAL FINANCE AND ENTERPRISE FINANCING CONSTRAINTS - Mamayusupova Shokhina Ulugbek kizi (Journal of Artificial Intelligence and Digital Economy, 2024)
In this study, we utilize panel data of A-share listed companies spanning from 2011 to 2020 to examine the effectiveness of the WW index in characterizing the level of enterprise financing constraints in China. Specifically, we explore the impact of regional digital finance (DF) development on these financing constraints. Our findings indicate that the WW index serves as a robust measure for assessing enterprise financing constraints. We observe that the development of digital finance has a substantial mitigating effect on these constraints, particularly benefiting small and medium-sized enterprises (SMEs) and private enterprises. Moreover, DF helps to address traditional finance's biases against private SMEs, such as size and ownership discrimination, as well as the mismatch of financial resources. Additionally, our results suggest that DF plays a crucial role in reducing information asymmetry in both the securities market and between banks and enterprises, thereby enhancing external financing capabilities. Furthermore, DF contributes to increasing total factor productivity (TFP) and optimizing internal financing capacity within enterprises. Overall, our study underscores the significant role of digital finance in alleviating enterprise financing constraints in China.